Safety and Efficacy of Repeat Doses of Allogeneic Mesenchymal Stem Cells in Patients with Age Related Frailty. (17th December 2021) - Saltzman, Russell; Schulman, Ivonne; Khan, Aisha; Hare, Joshua
Abstract: Age-related frailty is a common geriatric condition characterized by a decline in physical and immunological capacity that is associated with depletion of endogenous stem cells and leads to increased vulnerability for adverse health outcomes. Allogeneic mesenchymal stem cells (allo-MSCs) exert immunomodulatory effects and promote tissue repair, which may be able to impede the negative effects of the aging process. The objective of this study was to explore the safety and efficacy of repeated infusions of allo-MSCs in subjects with aging-frailty. Mean age at time of first and second infusions was 75.5 and 77 years of age, respectively. In this open-label clinical trial, 24 participants received two intravenous infusions of allo-MSCs with an average interval of 17.6 months between doses. Safety endpoints included incidence of treatment-emergent serious adverse events (TE-SAEs) within 1-month post-infusion and increase in Panel Reactive Antibodies (PRAs) at 6-months post-infusion. Primary efficacy endpoint was change in 6-minute walk test (6MWT) distance at 6-months post-infusion. No TE-SAEs occurred within 1-month post-infusion. PRAs remained stable throughout the study, indicating no evidence of immune rejection. 6MWT increased by 42 meters after the first infusion (P=0.018). Eighteen months later elevation persisted (P=0.026), but did not increase further after the second infusion. In summary, repeated intravenous infusions of allo-MSCs were safe in participants with age-related frailty and showed remarkable improvement in physical performance. Given the excellent safety and efficacy profiles demonstrated in this study, larger clinical trials are warranted to further quantify the efficacy of repeated dosing of allo-MSCs in this multisystem disorder.